Challenging Modernism through Hyperreality in Mosquitoes Play Script - Ragita Salma Wardhany (English Department, Faculty of Humanities, Andalas University, 2022)
The purpose of this research is to challenge the modernism view and principles by revealing the negative issues and impacts of technology as portrayed in Mosquitoes (2017) play script written by Lucy Kirkwood. The research uses a qualitative method in showing and elaborating the findings. To challenge the modernism view, the research undertaken uses postmodernism lens with Jean Baudrillard’s theory of simulation, simulacra, and hyperreality in analyzing situation and forms of those concepts which are hidden in the text. This research discovers that the advancement of technology makes the characters very dependent on technology itself, especially on computers, mobile phones, and the internet. However, this technological dependence is not accompanied by significant benefits as modernists assert, but rather tends to produce detrimental effects for the characters. The detrimental effect of using technology is that the characters are trapped in a world of hyperreality manifested in the form of fake news and cybercrimes, causing some serious problems that must be dealt with by them since the boundaries between real and fake have collapsed. This cause-effect regarding technology and hyperreality emphasizes a paradox that technology which is supposed to be controlled by humans yet control humans themselves because technology takes a role in shaping the way humans think and behave. In essence, the findings of this research reinforce that the positive view of modernism on advancement in human civilization is not fully materialized.